Australian Social Work Academics Respond to International Students in Crisis During COVID-19 - Fronek, Patricia; Briggs, Lynne; Liang, Jianqiang; Gallagher, Hilary; Doherty, Ainsley; Charles, Bronwyn; McDonald, Shane (Frontiers in Education, 2021)
This article discusses the impact of COVID-19 on a cohort of international students studying at one Australian university and the efforts made by social work academics to assist these students through a challenging and distressing time between December 2019 and July 2020. International social work students usually rely on scholarships and casual employment to support themselves while studying. Nonetheless, the Australian government made no financial provisions for international students when the COVID-19 pandemic struck leaving many students without any means of support. Students from all parts of the world attend Griffith University, located in south-east Queensland, Australia, including students from Wuhan, China, where the first known outbreak of COVID-19 was identified. Shame, anxiety, racism and concerns related to the wellbeing of families overseas were superimposed onto their own health concerns and day-to-day survival while still seeking to maintain academic progress. Material and emotional support were provided through the establishment of a food bank and the development of a case management model to address the needs of students. A COVID-19 Alternative Placement course and a field education student hub supported academic success during the health emergency. These interventions developed independently as a crisis response and were merged into a multi-pronged, coordinated approach that included collaborations with other sections of the university and the community. A School working committee was established to co-ordinate interventions to address individual student need that included crisis intervention, referrals to internal and external resources, and developing communities of support. The journey travelled by students and academics and the lessons learned from this experience are described, all of which are relevant to future health emergencies including the value of involving social work in university preparedness planning. The article concludes that intensive support can enhance resilience while supporting students’ own survival strategies, and, importantly, how such efforts can minimize, as far as possible, disruption to academic progress.